Реалізація стратегій і тактик спікера (на матеріалі парламентських дебатів Великої Британії) - Басюк, Леся Михайлівна; Basyuk, L. М. (Східноєвропейський національний університет імені Лесі Українки, 2014)
У статті здійснено спробу виявити роль і місце спікера в парламентських дебатах Великої Британії. Обґрунтовано вибір стратегій і тактик учасників парламентського дискурсу Великої Британії залежно від їхньої статусно-орієнтованої позиції під час парламентських дебатів. Визначено комунікативні стратегії і тактики спікера, спрямовані на досягнення перлокутивної мети – координації мовленнєвої поведінки адресата. Запропоновано алгоритм опису мовленнєвих актів як інструментів реалізації тактик спікера за різними параметрами. Здійснено спробу виявити та комплексно проаналізувати мовленнєві акти, обрані для реалізації тактик адресанта. The article attempts to identify the role and place of the Speaker in the UK parliamentary debates. The choice of strategies and tactics of participants in the parliamentary discourse in the UK is identified depending on their status-oriented position during the parliamentary debates. Defined communication strategies and tactics of the Speaker are aimed to achieve the perlocutionary goal – the coordination of verbal behavior of the addressee. The role of the Speaker in the parliamentary debates is assumed as a coordinator of the debating procedure and based on this determines his choice of coordination strategy of verbal behavior, which is aimed at regulating the addressee communicative speech behavior during the parliamentary debates. The strategy of coordination has the following tactics: presentation, regulation and reaction tactics. The algorithm description of speech acts based on various parameters as instruments to fulfil tactics of the Speaker is proposed in the article. Speech act (SA) is defined as the basic minimum unit of verbal communication; both intentionally and situationally induced, grammatically and semantically organized a statement that is accompanied by action of the Speaker directed at the addressee and his reaction. The attempt to analyze the speech acts chosen to fulfil tactics of the sender.
Realisation of Speaker’s Strategies and Tactics (Based on the Parliamentary Debates of Great Britain
Keywords: комунікативна стратегія; communication strategy; комунікативна тактика; communication tactic; парламентський дискурс; parliamentary discourse